Estudo das tecnologias de eficiência energética para redução de consumo de combustível automotivo com ênfase nas interações entre tecnologias com aplicação da metodologia DoE - Rosiana da Silva Lopes (2018)
This work presents a study of energy efficiency technologies applied in automotive vehicles considering the interactions between technologies. The fuel consumption of automotive vehicles is an important factor in current scenario, because in environment point of view the fossil fuels of conventional vehicles (gasoline and diesel oil) increase urban pollution worsening the greenhouse effect, in addition to contributing to the scarcity of oil reserves. With the aim to improve energy efficiency of vehicles, the automotive sector has invested on developing technologies that help decrease vehicles fuel consumption such the start stop system, low rolling resistance tire, between others called energy efficient technologies. However, when several energy efficiency technologies are applied simultaneously, the combined effect is smaller than expected when compared to each technology individually. This paper aims to evaluate the interactions between energy efficiency technologies applied in a vehicle in order to show how the interactions can reduce the technologies effect in the final product. The used methodology applies the experimental statistics tool DOE (Design of Experiments) to estimate the effect of each technology and the interactions between them. The results indicate that interactions are observed in technologies applied in powertrain and electric load system, while the technologies that reduce movement resistance forces (tire, aerodynamics and inertia) do not presented significant interactions. It was also observed that not including the interactions in the prediction of fuel consumption with application of energy efficiency technologies presents high errors, in the case of study of this work around 2.5% when the interactions are significant. It conclusion, the interactions of improvements on powertrain system need to be considered, using statistical tools while, improvements on movement resistance forces can be analyzed individually because the interactions related to these items can be despised